Formulation Development and Optimization of Rosuvastatin Loaded Nanosuspension for Enhancing Dissolution Rate - Rani, Asha; Verma, Ravinder; Mittal, Vineet; Bhatt, Shailendra; Kumar, Manish; Tiwari, Abhishek; Tiwari, Varsha; Pandey, Parijat; Kaushik, Deepak (Current Drug Therapy, 2023)
Background: Nanotechnology has been considered an auspicious approach over the last twenty years and numerous researchers are making efforts to extend its applications in pharmaceuticals. Recently, various nano-based drug delivery systems, such as nanoparticles, nanoemulgel, nanosuspension, and nanoemulsion, have been developed to deliver varieties of hydrophobics to target sites. Rosuvastatin is a competitive inhibitor of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase enzyme. The application of rosuvastatin is compromised because of its poor aqueous solubility and low oral bioavailability. Objective: This research work aimed to develop and characterize nanosuspension formulation for enhancement of the dissolution rate of rosuvastatin. Methods: Nanosuspension of rosuvastatin was prepared by using PVP K-30 and tween 80 as a stabiliser via the high-pressure homogenization method. The nanosuspension formulation was optimised by a factorial design to determine the effect of PVP K-30 (A), the concentration of tween 80 (B) and the number of the cycle (C) of high-pressure homogenizer on particle size (Y1), polydispersity index (Y2) and zeta potential (Y3) of the developed formulation. The optimised nanosuspension formulation of rosuvastatin was assessed for particle size, zeta potential, PDI, pH, % encapsulation efficiency of the drug, solubility study and comparative in vitro dissolution study. The optimised formulation passed the stability studies in terms of physical stability (sedimentation) for three months. Results: The optimised formulation resulted in 92.79 nm of particle size with a 0.201 polydispersity index. The nanosuspension of rosuvastatin showed higher dissolution rate as compared to the pure drug. Conclusion: This investigation demonstrated that nanosuspension preparation could be a promising approach for improvement of the dissolution rate of BCS II class drugs.
Keywords: zeta sizer